An experimental and theoretical magneto-structural study of polynuclear NiII complexes assembled from a versatile bis(salicylaldehyde)diamine polytopic ligand. Issue 15 (13th March 2015) - Oyarzabal, Itziar; Ruiz, José; Mota, Antonio J.; Rodríguez-Diéguez, Antonio; Seco, José M.; Colacio, Enrique
Abstract : Experimental and theoretical magneto-structural correlations and DFT calculations carried out in six novel Ni II complexes with uncommon structures. Abstract : Six novel Ni II complexes, ranging from mononuclear to tetranuclear, have been prepared from the polytopic symmetrical Mannich base ligand N, N ′-dimethyl- N, N ′-bis(2-hidroxy-3-formyl-5-bromo-benzyl)ethylenediamine (H2 L) and different anionic coligands: [Ni(H2 L)(NO3 )(H2 O)]NO3 ·H2 O (1 ), [Ni2 (μ-L)(acac)2 (H2 O)]·CH3 CN (2 ), [Ni2 (μ-L)(μ-OAc)(NCS)] (3 ), [Ni3 (μ-L)2 (μ-OH2 )2 (H2 O)(CH3 CN)](NO3 )2 ·4CH3 CN (4 ), [Ni4 (μ-L)2 (μ-OAc)2 (μ-OCH3 )2 ]·6H2 O·2CH3 OH (5 ) and [Ni4 (μ-L)2 (μ-OAc)2 (μ-N3 )2 ]·2H2 O·CH3 OH (6 ). These complexes have been characterized by single crystal X-ray diffraction, magnetic measurements and DFT theoretical calculations. The structural analysis of these complexes reveals that the anionic coligand and reaction conditions play a fundamental role in determining their final structures and magnetic properties. Compound1 contains a monomeric cationic unit with the nickel ion coordinated in the external O4 site of the compartmental ligand H2 L, which acts in a neutral zwitterionic form. Complexes2 and3 are dinuclear Ni2 neutral entities, in which the Ni II ions are connected through two μ-phenoxido bridging groups. The Ni(O)2 Ni bridging fragment in2 is almost planar, whereas in3 is bent due to the additional presence of a syn – syn acetate bridge connecting the Ni II atoms. Complex4 has a bent trinuclear structure with double μ-phenoxido/μ-water bridges between the central and terminal nickel atoms. Complexes5 and6 are Ni4 complexes with defective dicubane structures, in which triple μ-phenoxido/μ1, 1, 1 -X/ syn – syn acetate and double μ-phenoxido/μ1, 1, 1 -X mixed bridges connect central and terminal Ni II atoms, whereas double μ1, 1, 1 -X bridging ligands link the central Ni II ions (X = methoxido and azido groups for5 and6, respectively). Magnetic susceptibility measurements reveal that complex2 shows a moderate antiferromagnetic interaction between the Ni II ions through the double di-μ-phenoxido bridge, leading to a S = 0 ground state. Compared to2, complex3 shows a much weaker magnetic exchange interaction due the counter-complementarity effect provoked by the additional presence of the syn – syn acetate bridging group, as well as the non-planarity of the bridging fragment. In complex4, the double μ-phenoxido/μ-water mixed bridges lead to very weak antiferromagnetic interactions between the central and external Ni II ions. Overall ferromagnetic interactions are found for3, 5 and6, although in5 not all the magnetic pathways transmit ferromagnetic interactions. A detailed analysis of the magnetic exchange interactions transmitted through the different pathways as well as DFT calculations on the X-ray structures of compounds2–6 were performed to support the magneto-structural data of these compounds.